Pemberdayaan Kelompok Guru dalam Membuat Instrumen Pembelajaran Berdiferensiasi - Nurzengky Ibrahim; Desy Safitri; Sujarwo Sujarwo; Arita Marini; Musril Zahari (Institut Teknologi dan Bisnis Semarang, 2024)
Empowering groups of teachers in creating differentiated learning instruments can provide effective and meaningful learning experiences for each student, considering differences in abilities, learning speed, interests, learning styles and communication styles of each student. With differentiated learning, teachers can accommodate the needs of students who differ between individuals, which has implications for creating equal rights for students in the classroom during learning. The urgency of empowering this group of teachers is that each teacher must be able to apply differentiated learning in the classroom so that students can reach their maximum potential and be motivated in the learning process.